Analysis of Allelopathic Content in Acacia auriculiformis and Melia azadirachtah on Mung Bean Germination - Firman Ali Rahman; Taufik Arianto; Tabitha Sri Hartati Wulandari; Sulistijorini (Yayasan Tajuk Indonesia, 2024)
This study aims to analyze the effect of allelopathy from leaf extracts of Acacia auriculiformis and Melia azadirachta on the germination of mung beans (Vigna radiata). Alleleopathy is a biological phenomenon in which chemical compounds released by certain plants affect the growth and development of other plants. This study used an experimental method with various concentrations of leaf extracts of the two tree species (0%, 10%, 20%, and 40%). The parameters observed included germination percentage, growth rate, root length, and mung bean bud length. The results showed that the increase in the concentration of Acacia auriculiformis and Melia azadirachta leaf extracts significantly inhibited the germination process and early growth of mung beans. Allelopathic compounds such as flavonoids, tannins, and total phenols are thought to be the main cause of the barrier. Growth and development in acacia leaf extraction (Acacia auriculiformis) showed that the growth and development of green bean seeds experienced rapid growth, even exceeding growth in the control treatment. The difference in concentration in the analysis of further tests of neem leaf extraction and acacia gave a quite significant effect, in acacia leaf extraction there was no major effect on germination, but in neem leaf extraction on green beans which was given a negative effect on germination which at a concentration of 40% was much slower compared to other concentrations.